2006
DOI: 10.1007/s10209-006-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feedback and dwell time on eye typing speed and accuracy

Abstract: Eye typing provides a means of communication that is especially useful for people with disabilities. However, most related research addresses technical issues in eye typing systems, and largely ignores design issues. This paper reports experiments studying the impact of auditory and visual feedback on user performance and experience. Results show that feedback impacts typing speed, accuracy, gaze behavior, and subjective experience. Also, the feedback should be matched with the dwell time. Short dwell times re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 18 publications
2
89
0
6
Order By: Relevance
“…Furthermore, some previous evaluations of eye-typing and Dasher have been conducted with Finnish participants writing Finnish text (e.g. [8,9,12]). The structure of the Finnish language is very different from English and a previous research paper has reported that Finnish participants' English text entry was 16% slower than Finnish [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some previous evaluations of eye-typing and Dasher have been conducted with Finnish participants writing Finnish text (e.g. [8,9,12]). The structure of the Finnish language is very different from English and a previous research paper has reported that Finnish participants' English text entry was 16% slower than Finnish [3].…”
Section: Discussionmentioning
confidence: 99%
“…Wobbrock et al [20] found an average entry rate of 7 wpm with an uncorrected error rate of 4.62%, highly similar to our results. Majaranta et al [9] conducted three eye-typing experiments, two with a long dwell-timeout of 900 ms and one with a shorter dwelltimeout of 450 ms. The first two studies had a grand mean entry rate of 7 wpm.…”
Section: Discussionmentioning
confidence: 99%
“…This holds for the experiments with Dasher [11,14], and the same is true for soft keyboards. For instance, feedback modes have a significant effect on text entry speed [7]. The dwell time threshold similarly affects both the efficiency and the experienced workload [10].…”
Section: Why Are the Findings Across Studies So Different?mentioning
confidence: 99%
“…Although considerable research exists in eye tracking [3], [6], [9], [10], none has evaluated eye tracking with the ISO 9241 Ergonomic requirements for office work with visual display terminals (VDTs) -Part 9: Requirements for non-keyboard input devices. ISO 9241-9 establishes uniform guidelines and testing procedures for evaluating computer pointing devices.…”
Section: Introduction Iso 924-partmentioning
confidence: 99%